2013
DOI: 10.1186/2045-709x-21-43
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward evidence-based clinical practice among doctors of chiropractic with diplomate-level training in orthopedics

Abstract: BackgroundEvidence-based clinical practice (EBCP) is a practice model gaining prominence within healthcare, including the chiropractic profession. The status of EBCP has been evaluated in a variety of healthcare disciplines, but little is known regarding the attitudes doctors of chiropractic (DCs) hold toward this model of healthcare. This project examines the attitudes toward EBCP within a specialty discipline of DCs.MethodsWe identified a survey questionnaire previously used to evaluate EBCP among non-chirop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 31 publications
(33 reference statements)
2
26
0
Order By: Relevance
“…A sizeable proportion (a quarter to one third) also cited: ‘lack of industry support’; ‘lack of incentive’; ‘insufficient skills for interpreting research’; ‘locating and critically appraising research’; ‘lack of colleague support for EBP’; and ‘lack of relevance to chiropractic practice’. Many of the barriers identified in this study are similar to those found for chiropractors in Australia [ 19 ], Canada [ 20 ] and Great Britain [ 21 ] as well as a sub-specialty of chiropractic orthopedists in the US [ 22 ]. Interestingly, many of the same barriers are encountered in the medical and nursing professions [ 5 , 6 ], leading us to conclude that the challenges facing the chiropractic profession in implementing EBP are not unique.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…A sizeable proportion (a quarter to one third) also cited: ‘lack of industry support’; ‘lack of incentive’; ‘insufficient skills for interpreting research’; ‘locating and critically appraising research’; ‘lack of colleague support for EBP’; and ‘lack of relevance to chiropractic practice’. Many of the barriers identified in this study are similar to those found for chiropractors in Australia [ 19 ], Canada [ 20 ] and Great Britain [ 21 ] as well as a sub-specialty of chiropractic orthopedists in the US [ 22 ]. Interestingly, many of the same barriers are encountered in the medical and nursing professions [ 5 , 6 ], leading us to conclude that the challenges facing the chiropractic profession in implementing EBP are not unique.…”
Section: Discussionsupporting
confidence: 56%
“…This is one of the largest studies to examine chiropractors’ perspectives relative to EBP, and to our knowledge, the first national survey to be conducted in the United States. One other EBP study was performed in the US, however the sample was limited to mid-western chiropractors with advanced training in orthopedics [ 22 ]. Despite the large absolute sample size of our survey (n = 1,314), it represents only a small relative cross-sectional sample of the American chiropractic profession (n = 60,000) [ 27 - 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies found that chiropractors generally held positive attitudes towards EBP, and were interested in improving their EBP skills [ 36 40 ]. Nonetheless, application of EBP in clinical practice appears to be suboptimal, with only a small majority of American chiropractors (53 %) reporting that about half of their practice was based on research evidence [ 40 ].…”
Section: Resultsmentioning
confidence: 99%